Economic openness and territorial politics in China - Sheng, Yumin (Cambridge University Press, 2010)
"Why and how has the Chinese central government so far managed to fend off the centrifugal forces under rising globalization that are predicted to undermine national-level political authority everywhere? When institutionally empowered by centralized governing political parties as in China, national politicians confronting the menace of economic openness will resort to exercising tighter political control over the subnational governments of the "winner" regions in the global markets. Although its goal is to facilitate revenue extraction, redress domestic economic disparity, and prolong the rule of national leaders, regionally targeted central political control could engender mixed economic consequences at the subnational level. Yumin Sheng examines the political response of the Chinese central government, via the ruling Chinese Communist Party, to the territorial challenges of the country's embrace of the world markets, and the impact of the regionally selective exercise of political control on central fiscal extraction and provincial economic growth during the 1978-2005 period"-- Provided by publisher.